METODE SOSIODRAMA UNTUK MENINGKATKAN KEMAMPUAN SISWA MADRASAH ALIYAH SWASTA UNGGUL NURUR-RASYAD AL-AZIZIYAH TIJUE - Teuku Sanwil (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
The purpose of this article is to find out the differences in learning outcomes of students who use the sociodrama method and how big is the increase in Mahārah al-Kalām to students who apply the sociodrama method in Arabic learning that has some maharah as their basic competencies. This is an experimental study, where the research subjects are students of Madrasah Aliyah or Islamic high school. Two homogeneous groups were taken as samples; Class XI-1 as an experimental class and Class XI-II as a control group. This research uses Randomized Pretest- Posttest Control Group Design as its research design. The results in this article are based on the results of statistical analysis which shows that the T- Posttest between the control and experimental groups shows that the value of T-count = -4.503 <T-table = 2.037 (Ha is accepted) which means that there are significant differences of the learning outcomes between the control group and the experimental group. Whereas the T-test of pretest and posttest of the experimental group resulted in a calculated T-value = 13,348 <T-table = 2,035 (Ha is accepted), which means that there was a significant increase in student learning outcomes in the experimental group.